Financial Determinants of Qardhul Hasan Financing Growth: Evidence from Islamic Banks in Indonesia - Agus Saur Utomo; Novita Kusuma Maharani; Danes Quirira Octavio (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2015)
The purpose of this paper is to investigate the financial factors that determine the growth of qardhul hasan financing in the sharia banks in Indonesia. We employ financial ratios such as Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Net Interest Margin (NIM), Operational Cost to Operational Income (BOPO), Return on Asset (ROA) and Return on Equity (ROE) to explain the growth of qardhul hasan during 2011 to 2014. This paper utilizes the fixed effect model and the random effect model to provide empirical evidences. The empirical result demonstrates that Non-Performing Financing (NPF), Net Interest Margin (NIM), Return on Asset (ROA) and BOPO have significance relationship to the qardhul hasan financing. The finding shows that the growth of qardhul hasan financing in sharia banks is influenced by financial ratios of NIM, NPF, BOPO and ROA. This finding adds important evidence to the existing research on qardhul hasan financing in sharia banks.